Silenced Voices: Strategies of Exclusion and Inclusion in the Coverage of Sexual Violence in Indonesian Online Media - Neneng Hartini; Agus Hamdani (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to describe the representation strategy of victims of sexual violence in online media coverage using the Critical Discourse Analysis (AWK) approach of the Theo van Leeuwen model. The object of study is five news articles from national online media, Kompas.com, Tempo.co, Merdeka.com, Detik.com, and Metrotvnews.com, that raised the case of rape by students of the Padjadjaran University specialist doctor education program (PPDS). The method used is descriptive qualitative with critical discourse text analysis techniques, including exclusion and inclusion strategies, such as passivation, nominalization, objectivation, identification, and assimilation. The results showed that in most news, the perpetrators were described explicitly by mentioning their social status and institutional affiliation. At the same time, the victims were often presented vaguely and subordinated in the sentence structure. This finding shows that the media has not fully sided with the perspective of victims, so the news has the potential to influence public perceptions of victims of sexual violence negatively. The implications of this research are recommended as teaching materials for news texts in Indonesian language learning at the high school level to form media literacy and students' critical perspectives on the issue of sexual violence.